Reputational intelligence: innovating brand management through social media data. - Casado-Molina, Ana María; Ramos, Célia M.Q.; Rojas-de-Gracia, María Mercedes; Peláez-Sánchez, José Ignacio (Emerald, 2020)
Purpose – Companies are currently facing the challenge of understanding how their business is affected by the large volume of opinions continually generated by their stakeholders in social media regarding their intangible assets (experiences, emotions and attitudes). With this in mind, the purpose of this paper is to present an innovative management model, named E2AB, to measure and analyse reputational intangibles from digital ecosystems and their impacts on tangible assets. Design/methodology/approach – The methodology applied was big data and business intelligence techniques. These methods were used in the computing process to obtain daily data from every asset guarantees that the model is validated with robust data. This model has been corroborated using data from the banking sector, specifically 402,383 net data inputs from the digital ecosystems. Findings – This study illustrates the existence of a holistic influence of intangible assets over tangible assets. The findings demonstrate complex relationships between tangible and intangible assets, determined not only by the type of variable but also by its valence and intensity. Practical implications – These findings may help chief communication officers and general managers a better understanding of how intangible assets extracted from online users’ opinions are related to their organisation’s tangible assets plus a chance to find out about their impact and how to manage them for a practical and agile decision making in real time. Originality/value – It is a pioneering work in establishing a model, which demonstrates transversal and holistic relationships between relational intangible and tangible assets of firms from digital ecosystems, using business intelligence techniques.
https://openpolicyfinder.jisc.ac.uk/id/publication/2703?from=single_hit
Keywords: Reputación digital; Imagen corporativa; Redes sociales en internet; Business intelligence; Social media data; Reputational intelligence; Reputational model; Intangible management; Customer perceptions